Characteristics of COVID-19 Patients in Haji Adam Malik General Hospital, Medan, North Sumatera - Dyana Destylya; Bintang YM Sinaga; Parluhutan Siagian; Putri Chairani Eyanoer (Respiratory Science, 2022)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The increase in the number of COVID-19 cases was happening quite quickly and has spread between countries so that COVID-19 has become a pandemic in the world. This study aimed to determine the characteristics of COVID-19 patients at Haji Adam Malik General Hospital Medan. Method: This was a descriptive study. Data were taken from the medical records of 110 hospitalized patients with positive RT-PCR results for COVID-19 from December 2020 to April 2021. The inclusion criteria for the case samples were patients diagnosed with COVID-19 based on RT-PCR and the exclusion criteria were incomplete medical records. Characteristic analysis was carried out using the Kruskal Wallis test. Results: The most common comorbidities found in patients with severe COVID-19 were diabetes mellitus and HIV. The most common comorbidity found in moderate-level COVID-19 patients was pregnant women. The most common chest X-rays finding in severe and critical levels was bilateral infiltrates. Recovered patients were mostly obtained at moderate level, while deceased patients were mostly observed at critical levels. Conclusion: Characteristics of COVID-19 patients at Haji Adam Malik General Hospital were classified based on the degree of disease by age, lymphocyte value, N/L ratio, levels of CRP, D-dimer, procalcitonin, fibrinogen, ferritin, and comorbidities as well as the appearance of infiltrates in both lung fields.